Corporate governance and Islamic law compliance risk - Hasan Mukhibad; Ahmad Nurkhin; Kuat Waluyo Jati; Prabowo Yudo Jayanto (Cogent Economics & Finance)
This study examines the influence of the Shariah Supervisory Board (SSB), Board of Directors (BOD), Risk Officers (RO), Audit Committee, and market competition (Lerner) on the Islamic Law Compliance Risk (ILCR). We use a sample of full-fledged Islamic banks in Indonesia with an observation period of 2009–2019. Data analysis uses Fixed Effect Model (FEM). Our results show that SSB and BOD are not proven to be able to control ILCR. ILCR can be decreased by increasing the number of audit committees and the proportion of independent RO. In addition, the Lerner index has a positive influence ILCR. The results of the robustness test also confirm the results of this study. This research extends the previous studies on evaluating the risk-taking of Islamic Banks beyond the common risk (insolvency, liquidity, credit, and market), particularly the unique risks faced by Islamic banks. This study recommends increasing the effectiveness of SSB and BOD supervision on bank operations, increasing the ILCR.